Auditory Cognitive Function Assessment during Pregnancy: An Event-Related Potential and Neuropsychological Study (Bangladesh Journal of Medical Science, 2021)
Objectives: We investigated the auditory cognitive and behavioral functions during 2nd and 3rd trimesters of pregnancy using event-related potentials (ERPs) and different neuropsychology tests, respectively.Methods: The ERPs were studied by using a 128-sensor net, and PAS/COWA, WCST, ZCT, RAVLTIM/RAVLTDR/RAVLTTS, and BDI were tested for neuropsychology assessment. Total 39 subjects were recruited for control group (G1, n=15, non-pregnant), 2nd trimester group (G2, n=12, 13-26 weeks gestation), and 3rd trimester group (G3, n=12, 26- 40 weeks gestation). Auditory oddball paradigm was used during ERP study. Subjects silently counted only the target stimuli with attention by ignoring standard stimuli. Value of the mean differences of the target and standard stimuli were measured across groups in 10-20 electrode systems.Results: The P50, N100, and P300 ERP components were analyzed. The G3 (at F7 and C3) and G2 (at T4) groups evoked the highest significant amplitudes in P50, and G3 (at Cz and Pz) and G1 (at F8 and T4) evoked the highest significant amplitudes of N100 with significantly prolonged latencies at Cz and O1 (in G1) and F8 (in G2). However, significantly higher amplitudes of P300 were found at Fz (in G3) and FP1 (G2) (G2>G3). On the other hand, neuropsychology tests revealed that G2 possessed the highest significant score in WCST and G1 in ZCT. The G3 performed poorly in all tests.Conclusion: We concluded that pregnant groups performed better in auditory (attention/memory) and executive function assessment. Moreover, the 2nd trimester group has better auditory cognitive function compared to the 3rd trimester group due to the effect of hormonal changes during pregnancy, which might be a positive influence during the pregnancy period.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.608-617